"Evaluation of the EndoChoice full spectrum endoscopy (Fuse) platform for upper endoscopy and colonoscopy". (2nd April 2016) - Gralnek, Ian M.
ABSTRACT: Traditional forward-viewing (TFV) flexible gastrointestinal endoscopes currently used to perform esophagogastroduodenoscopy (EGD) and colonoscopy have changed relatively little in the past two decades. While considered the standard of care, TFV endoscopes only allow between a 140-170° field of view (FOV). A revolutionary new endoscopic technology, "full spectrum endoscopy (Fuse)", now allows a panoramic 245 o (gastroscope) to 330° (colonoscope) FOV. With this new endoscopic platform, physicians are able to view formerly difficult- or impossible-to-view areas within the gastrointestinal (GI) tract, such as behind the pylorus/within the duodenal bulb or the proximal side of colonic folds/flexures.